Analysis of various Plant Disease detection Techniques - Thukral, Gazzal; Chand, Lal (International Journal of Computer Sciences and Engineering, 2019)
The plant disease detection is the approach which is applied to predict disease type from the input image. The plant disease detection has the two phases which are feature extraction and classification. In the previous years, various techniques has been designed for the plant disease detection. The various classifications methods has been designed for the plant disease detection like SVM, decision etc. In this paper, various plant disease detection techniques are reviewed and analyzed in terms of certain parameters.